Immediate transformation to online teaching of the Kingdom University as a consequence of COVID-19 - DARWISH, S.; Al BATSAKI, N.; TERRO, M. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Most universities and educational institutions follow conventional learning. E-learning utilizes electronic technologies to deliver curriculum beyond traditional means, which presents many challenges. E-learning is also a way to access all programs and receive awards for certificates and degrees online. It presents a formidable communication media between teachers, professors, and students attending online classes. This paper focuses on the objectives and mechanisms to achieve the necessary changes to accomplish the required learning objectives. It will also highlight the challenges facing the students, instructors, and decision-makers at executive levels in educational institutions. RESUMEN La mayoría de las universidades e instituciones educativas siguen el aprendizaje convencional. El e-learning utiliza tecnologías electrónicas para ofrecer un plan de estudios más allá de los medios tradicionales, lo que presenta muchos desafíos. El aprendizaje electrónico también es una forma de acceder a todos los programas y recibir premios por certificados y títulos en línea. Presenta un formidable medio de comunicación entre profesores, profesores y alumnos que asisten a clases en línea. Este artículo se centra en los objetivos y mecanismos para lograr los cambios necesarios en los objetivos de aprendizaje requeridos. También en destacar los desafíos que enfrentan los estudiantes, instructores y tomadores de decisiones en los niveles ejecutivos de las instituciones educativas.